11-Oxygenated androgens are not secreted by the human ovary: in-vivo data from four different cases of hyperandrogenism. Issue 6 (23rd November 2022) - Auer, Matthias K; Hawley, James M; Lottspeich, Christian; Bidlingmaier, Martin; Sappl, Andrea; Nowotny, Hanna F; Tschaidse, Lea; Treitl, Marcus; Reincke, Martin; Keevil, Brian G; Reisch, Nicole
Abstract: Objective: Differentiation of an adrenal from an ovarian source of hyperandrogenemia can be challenging. Recent studies have highlighted the importance of 11-oxygenated C19 steroids to the androgen pool in humans. The aim of this study was to confirm the origin of 11-oxygenated androgens in females and to explore their potential use in the diagnostics of hyperandrogenic disorders. Methods: We measured testosterone and its precursors (dehydroepiandrosterone-sulfate and androstenedione) and 11-oxygenated androgens (11β-hydroxyandrostenedione (11-OHA4) and 11-ketotestosterone (11-KT)) in the periphery, adrenal and ovarian veins in four different cases of hyperandrogenism in females (polycystic ovary syndrome (PCOS), primary bilateral macronodular adrenal hyperplasia, Sertoli–Leydig cell tumor and ovarian steroid cell tumor). Results: Two patients demonstrate excessive testosterone secretion in neoplastic ovarian tumors which was not paralleled by a significant secretion of 11-oxygenated androgens as determined by adrenal and ovarian vein sampling. In androgen-secreting bilateral adrenal macronodular hyperplasia, steroid profiles were characterized by elevated 11-KT and 11-OHA4 concentrations in adrenal veins and the periphery. In the patient with PCOS, peripheral 11-KT concentrations were slightly elevated in comparison to the other patients, but the 11-KT and 11-OHA4 concentrations were comparable in ovarian veins and in the periphery. Conclusion: This study confirms that 11-OHA4 and 11-KT are not biosynthesized by the ovary. We propose that the testosterone/11-KT ratio as well as 11-OHA4 could help identify predominant adrenal androgen excess and distinguish neoplastic and non-neoplastic ovarian androgen source. Significance statement: This study confirms that 11β-hydroxyandrostenedione (11-OHA4) and 11-ketotestosterone (11-KT) are not biosynthesized by the human ovary. We propose that the testosterone/11-KT ratio as well as 11-OHA4 could help to identify predominant adrenal androgen excess and distinguish neoplastic and non-neoplastic ovarian androgen source.